(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To avoid dependency & environmental pollution, inthe recent& upcoming years IC engine-based vehicleswill be replaced with battery operated vehicles. More research is going in E- Vehicle & its subsystemlike Battery, Motor, Motor drive, Battery Charger, etc. Major challenges of E-vehicle are minimum charging time of battery with optimum life span. SMPS based battery charger is one of the solutions for battery charging. In this paper a comprehensive review aboutfeasibility &development checks of Switch Mode Power Supply (SMPS) based charger and its subsystems. Method and topology review of different charger circuits, Selection criteria of different component used in circuitsand development of (SMPS) charger circuits. Along with that development of charger circuit which further used in charger. Elaboration about different charging method & operation of charger.